FRI0256 Significance of Cognitive Impairment in Systemic Sclerosis. (15th July 2016) - Groseanu, L.; Gudu, T.; Balanescu, A.; Bojinca, V.; Opris, D.; Saulescu, I.; Borangiu, A.; Constantinescu, C.; Predeteanu, D.; Berghea, F.; Negru, M.M.; Vlad, V.; et al.
Abstract : Background: There is an increased appreciation of the burden of cognitive impairment in people with autoimmune diseases (1). Recent studies have demonstrated that patients with systemic sclerosis (SSc) have a specific pattern of cognitive impairment: the dysexecutive syndrome (2). Objectives: We evaluated the prevalence of cognitive impairment in SSc and assessed the association with the disease features and impact on daily living Methods: Consecutive SSc from EUSTAR center 096 were examined. Montreal Cognitive Assessment (MoCA) was used to assess cognitive dysfunction and scores ≤26 were considered abnormal (3). SSc patients were assessed according tu MEDS evaluation sheets to determine organ involvement, autoantibody profile, disease activity (Valentine Activity Index) and disease severity (Medsger Severity Index). sHAQ (Scleroderma Health Assessment Questionnaire) has also been completed. Data were compared by difference tests according to the types of variables: t-test, Mann-Whitney or chi-square. To evaluate correlations between variables Pearson or Spearman correlations were used. Results: A total of 70 SSc patients [36 (51.42%) limited SSc (lSSc) and 34 (48.57%) with diffuse SSc (dSSc), 60 female; mean age 54.5 (±11.62) years; mean disease duration 66 (±429.6) months] were included in the study. 47.14% of the patients had active disease, the mean Rodnan score was 7 (±4.17), the mean Medsger score was 5.5 (±2.89), 24.28% of the patients had lung involvement and 20% had pulmonary arterial hypertension. The mean HAQ was 1 (±0.59). Cognitive impairment was identified in 65.71% SSc patients; the mean MOCA score was 26 (±2.83). Cognitive impairment of SSc patients was related to older age (r=-0.378, p=0.001), rural provenience (r=-0.351, p=0.003), severity of the disease evaluated by the Medsger score (r=–0.262, p=0.029) and poor quality of life evaluated by sHAQ (r=-0.323, p=0.003).Correlations were also identified with musculoarticular involvement (r=-0.330, p=0.006), advanced capillaroscopy patttern (r=-0.331, p=0.006). The diiffuse SSc patients were more likely to have cognitive dysfunction (likehood ratio 0.012) as were those with SCL70 positive (0.0.18). No relationship was identified between cognitive impairment and lung, heart or renal involvement, the presence of digital ulcers, the use of corticosteoids or immunosuppression. Conclusions: An increased prevalence of cognitive impairment was observed in SSc and associated with age, rural provenience, more severe disease, muscle involvement and poor quality of life. Further studies are needed to be compared with healthy controls and to assess the role of microvascular damage or that of other confounders. References: T.N.Amaral et al. Prevalence and significance of cognitive impairment in systemic sclerosis Ann Rheum Dis 2015;74:605 Ylmaz N. et al Dysexecutive syndrome: a specific pattern of cognitive impairment in systemic sclerosis Cogn Behav Neurol. 2012 Jun;25(2):57–62. www.mocatest.org/normative-data/ Disclosure of Interest: None declared